FIRST-PRINCIPLES INVESTIGATION OF THE ELECTRONIC STRUCTURE AND OPTICAL RESPONSE OF Ga2S3 AND Ga2Se3 CHALCOGENIDES - Nwachuku, Doris Ngozi (FUDMA Journal of Sciences, 2025)
Gallium sulfide (Ga₂S₃) and gallium selenide (Ga₂Se₃) vacancy defect binary materials in the monoclinic Cc phase with a four formula units in a unit cell have been investigated within the density functional theory (DFT) framework. DFT (LDA +U), with PAW pseudopotentials in the Abinit (v7.10); plane-wave cut-off of 15 Ha, k-point grid of 4x4x4 were used in the calculations. Both Ga₂S₃ and Ga₂Se₃ were identified as semiconductors, exhibiting direct band gaps at the Γ- point, with values of 2.86 eV ( and 1.47 eV , respectively. These results are in agreement with the experimental values of Ga₂S₃ 2.48 eV (Işık et al, 2018) and Ga₂Se₃ 1.99 eV (Huang, 2013). Orbital contributions to the DOS reveal that, in Ga₂S₃, the VBM is dominated by S-3s states, whereas the CBM is mainly derived from Ga-4s and S-3p states. In Ga₂Se₃, the VBM arises chiefly from Se-4s states, while the CBM is primarily composed of Ga-3d and Se-4p states. Dielectric response function calculations yielded (0) of 4.9 and 6.0 for Ga₂S₃ and Ga₂Se₃ respectively. These narrow bandgaps enable efficient absorption in the visible range for solar energy conversion and light-emitting applications. The results offer a theoretical foundation for additional experimental research on these materials. It is recommended that temperature-dependence and optical absorption spectra be investigated using other computational methods to assess optoelectronic applications.